Radiological appearance of cortical desmoid in a 14-year-old male patient: A case report - Khalid Ibrahim; Osama Elhag; Reem AlKetbi; Amna AlKetbi; Loai Ali (Radiology Case Reports)
Cortical desmoid is an uncommon benign bony lesion that can typically be diagnosed through conventional radiographic methods. However, here we present an atypical case of a 14-year-old male who presented with a history of trauma, and the initial X-ray showed a right femur suspicious bony lesion. Still, the subsequent use of CT and MRI confirmed the diagnosis of cortical desmoid, so conservative management and follow-up imaging was recommended. This case highlights the importance of proper identification of this entity can prevent unnecessary biopsy and surgical intervention.